A construção da heteronormatividade em personagens gays na telenovela - Sanchez, Marcelo Hailer (2013)
This research aims to analyze the construction of gay characters in narratives displayed in the range night Globo. This is to demonstrate how are strongly marked by heteronormativity, understood as the organization of male sexuality, and how the privilege of this standard becomes invisible even homosexuality in the novels overall. We hypothesized that, unlike what happens with heterosexuality, which organizes homosexuality as an opposite, heteronormativity does not include opposition or heteronomy. The gay characters as discursive device to strengthen the rules of the Matrix heteronormative. The research corpus comprises the novels America (2006), Two Faces (2007/08), Tropical Paradise (2007) and Foolish Heart (2011), to be examined from the angle of its forward or backward in relation to the representation of the body dissident gay. The base of theoretical studies of Michel Foucault about the construction of normative discourses and scholars of communication within the cultural industry such as Edgard Morin and Theodor Adorno. The methodology used and the historical survey decoupage dialog